2013
DOI: 10.1073/pnas.1219142110
|View full text |Cite
|
Sign up to set email alerts
|

Using a preclinical mouse model of high-grade astrocytoma to optimize p53 restoration therapy

Abstract: Based on clinical presentation, glioblastoma (GBM) is stratified into primary and secondary types. The protein 53 (p53) pathway is functionally incapacitated in most GBMs by distinctive type-specific mechanisms. To model human gliomagenesis, we used a GFAPHRas V12 mouse model crossed into the p53ER TAM background, such that either one or both copies of endogenous p53 is replaced by a conditional p53ER TAM allele. The p53ER TAM protein can be toggled reversibly in vivo between wild-type and inactive conformatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 52 publications
2
34
0
1
Order By: Relevance
“…Indeed, Tessoulin et al 12 showed that endogenous levels of glutathione correlated with APR-246 sensitivity in multiple myeloma cells, while in astrocytoma, the absence of p14 ARF expression, an endogenous MDM2 inhibitor, was associated with resistance to APR-246 32. Importantly, Aryee et al 33 proposed a panel of 42 apoptotic genes that may predict APR-246 response in sarcoma cells.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, Tessoulin et al 12 showed that endogenous levels of glutathione correlated with APR-246 sensitivity in multiple myeloma cells, while in astrocytoma, the absence of p14 ARF expression, an endogenous MDM2 inhibitor, was associated with resistance to APR-246 32. Importantly, Aryee et al 33 proposed a panel of 42 apoptotic genes that may predict APR-246 response in sarcoma cells.…”
Section: Discussionmentioning
confidence: 99%
“…The restoration of p53 has strong anti-tumor effects in Tu-OPCs and human glioma cells suggest that targeting p53 in glioma may prove useful in the clinic. Our findings are in line with recent work demonstrating that p53 restoration is efficacious for astrocytomas (Shchors et al, 2013). Furthermore, of the 20% of glioma patients harboring p53…”
Section: D22 Restoration Of P53 and Nf1 Have Strong Anti-tumor Effectssupporting
confidence: 93%
“…OPCs at pre-malignant stages (Schwartzbaum et al, 2006;Shchors et al, 2013;Zhu and Parada, 2002). While NF1 controls the expansion, proliferation, and differentiation of OPCs early on, p53 clearly plays a later but vital role in preventing OPC transformation since NF1-null OPCs never transform despite their overwhelming expansion in the brain parenchyma.…”
Section: D21 Individual Roles Of P53 and Nf1 During The Progression mentioning
confidence: 99%
“…However, although it has significant effect in prolonging the lifespan of some patients with glioma, the efficacy of TMZ for treating certain GBM patients is limited (14), and TMZ resistance may result in a poor prognostic outcome in patients with GBM. Several mechanisms, including DNA repair mechanisms (15), high expression of epidermal growth factor receptor (16), the mutation of p53 (17) and the deficiency of phosphatase and tensin homolog (18), are involved in TMZ resistance. However, in a previous study, one-third of patients exhibited hypermethylation of methylguanine-DNA methyltransferase promoter, signifying sensitivity toward alkylating agents (19).…”
Section: Discussionmentioning
confidence: 99%